Superior vena cava syndrome management in limited source setting: a case report - Setiawan, Indra; Sunaka, I. Wayan; Yaniswari, Ni Made D. (International Journal of Advances in Medicine, 2022)
Superior vena cava syndrome (SVCS) is syndrome caused by mass compression, tumor invasion, and/or thrombosis of SVC. In the past, SVCS was mostly linked to infection. Nowadays, SVCS is mostly linked to malignant tumor and medical procedures. Most common malignant cause of SVCS is non small cell lung cancer. A 69-year-old man was presented with breathing difficulty. Symptom began 4 months before admission, with worsening of symptom since 2 weeks before admission. Symptom improved with sitting position, and worsened with supine position. Patient had been sleeping with 2 pillows. Patient had productive cough and hoarseness. Swelling of face and neck were present. Collateral vein distention was visible in the area of head, neck, and chest. Physical examination of lung revealed decreased vesicular breath sound at right side. Non pitting edema was found at both sides of upper extremity. SVCS in this case can be categorized into grade 2, chronic SVCS case. CT showed center right lung mass, although malignant cells were not obtained from pleural puncture and CT guided needle biopsy. Staging of mass was T4N3M1a. Mass finding at the center of right lung is in accordance with the previous findings that SVCS generally arise from lung (not mediastinum), and that right sided masses are generally more likely to cause SVCS. Management in this case was done by giving corticosteroid and diuretic. Surgery, radiotherapy, and immunotherapy were not done since malignancy diagnosis hadn’t been able to be concluded.